Electro‐immunosensor for ultra‐sensitive determination of cardiac troponin I based on reduced graphene oxide and polytyramine. Issue 2 (24th November 2022) - Brussasco, Jéssica G.; Guedes, Pedro H. G.; Moço, Anna C. R.; Moraes, Dayane D.; Flauzino, José M. R.; Silva, Heliane S.; Silva, Atair C.; Silva, Jonathan P.; Madurro, João M.; Brito‐Madurro, Ana G.
Abstract: This work reports the construction of a novel nanostructured immunosensor for detection of the troponin I biomarker (cTnI). Anti‐troponin I antibody was anchored on the modified graphite electrode with reduced graphene oxide and polytyramine for detection of troponin I in serum samples. The performance of the electro‐immunosensor was evaluated by differential pulse voltammetry. The immunosensor presented a wide work range, from 4 ng mL −1 to 4 pg mL −1, whose detection limit (4 pg mL −1 ) is significantly lower than the basal level in human serum, and maintained 100% of response after 30 days of storage. Moreover, the immunosensor showed good selectivity for detection of cTnI in real sample containing interfering substances and specificity of response to cTnI in the serum of healthy and sick patients, and demonstrated the possibility of reuse for two consecutive analyses, in addition to using a simplified and inexpensive platform when compared to other devices, demonstrating them excellent potential for application in diagnosis in the early stages of acute myocardial infarction. Abstract : Scheme of construction steps of the immunosensor where a platform containing GE/rGO/pTyr/anti‐cTnI/cTnI is indirectly detected using differential pulse voltammetry.